Application of optical tweezers in cardiovascular research: More than just a measuring tool - Yang, Yi; Fu, Zhenhai; Zhu, Wei; Hu, Huizhu; Wang, Jian’an (Frontiers in Bioengineering and Biotechnology, 2022)
Resent advances in the field of optical tweezer technology have shown indispensable potential in its applications in cardiovascular medicine, bringing this laboratory-based nanomechanical instrument into the spotlight of translational medicine. This article summarizes findings in the cardiovascular system using the optical tweezer, including not only finite nanomechanical measuring but also multifunctional manipulation of biological active molecules such as myosin and actin, of cells such as red blood cells and cardiomyocytes and subcellular organelles, as well as of microvessels in vivo. Implications of these findings in diagnosis and treatment of diseases, as well as potential prospectives that could also possibly benefit from this tool, are also discussed.